Hitchcock's Motifs - Walker, Michael (Amsterdam University Press, 2021)
Among the abundant Alfred Hitchcock literature, Hitchcock's Motifs has found a fresh angle. Starting from recurring objects, settings, character-types and events, Michael Walker tracks some forty motifs, themes and clusters across the whole of Hitchcock's oeuvre, including not only all his 52 extant feature films but also representative episodes from his TV series. Connections and deeper inflections that Hitchcock fans may have long sensed or suspected can now be seen for what they are: an intricately spun web of cross-references which gives this unique artist's work the depth, consistency and resonance that justifies Hitchcock's place as probably the best know film director ever. The title, the first book-length study of the subject, can be used as a mini-encyclopaedia of Hitchcock's motifs, but the individual entries also give full attention to the wider social contexts, hidden sources and the sometimes unconscious meanings present in the work and solidly linking it to its time and place.